Analysis of Land Information Maps Using Participatory Mapping Methods (Case Study: Mejoyolosari, Jombang) - Tiya Anita P; Yanto Budisusanto (Institut Teknologi Sepuluh Nopember, 2019)
Based on the regulation of the Minister agrarian and Space of the Republic Indonesia number 12 of 2017 and presidential instruction Number 2 of 2018 for accelerating Pendaftaran Tanah Sistematis Lengkap (PTSL). In order to mapping the land parcels, it is necessary to have the data of the subject and the object of the land so that the Land Map information will be developed. The identification and validation parcels of land parcels are carried out using participatory mapping method. The Participatory Mapping Method used is to delineate the boundary of the land parcels on the Work Map (Pleiades, high-resolution satellite imagery) The delineation result from the participative mapping is further validated in the field by taking 48 samples of the land parcels. In this research, the land map and land information (Land Record) are available, information on the distribution of registered and unregistered land parcels. And obtained the results of extensive accuracy of Delineation with direct measurements of the field according to BPN Standarization. Delineation of Pleiades high-resolution satellite images land parcels sample that meets the wide accuracy of 19 land parcels of soil, 11 fields of rice fields and 8 residential areas.